Pop-Up Ads Legal, Illegal, and The Role of The Financial Services Authority - Widyasari, Zahra Nurizki; Budiono, Arief; Ramon, Tomás Mateo (Universitas Muhammadiyah Malang, 2024)
Pop-up ads are notifications on the smartphone window when opening a website or application, which are useful for attracting users when crossing the web. Legal and illegal online loans also utilize this feature in marketing their services. The Financial Services Authority has a vital role in eradicating these pop-up ads so as not to cause unrest in the community. The aim is to find out how the role of the Financial Services Authority in controlling the circulation of online loan pop-up ads and what the consequences are. This literature study research uses normative juridical research methods. The data combines primary, secondary, and tertiary legal sources, then processed through descriptive analysis to obtain detailed and structured results. The results show that pop-up ads for online loans, especially illegal ones, can bring unrest to the community. Therefore, people can be easily tempted to take out loans and end up badly when they cannot repay them. The reasons behind a person making a loan vary, such as attractive advertisements or urgent economic circumstances. The Financial Services Authority and other government agencies are working together to eradicate illegal online loans, one of which is blocking them so that only verified online loan pop-up ads remain. The hope is that the public does not need to worry about accessing online loans through pop-up ads because it can be ascertained that these loans are legal. This research concludes that online loan pop-up ads are still so troubling that the role of the Financial Services Authority and other government agencies needs to be improved. The Financial Services Authority must not be careless in eradicating them to create a healthy and safe economic environment for the community.